LOCAL WISDOM OF SIRI' NA PACCE ON ETHICAL PRACTICES OF THE ACCOUNTING PROFESSION AT THE NURUDDIN TEMAPPA MOSQUE KEC. SUPPA - Fania, Fira; Hamid, Abdul; Rismala (Islamic Financial And Accounting Review, 2023)
The Siri' Na Pacce culture related to accounting is called Cultural Accounting. Siri' Na Pacce is a form of self-esteem and a high sense of shame. This is used as unity or solidarity among the Bugis, Makassar, Mandar and Toraja ethnic communities and as a guideline in daily life and good behavior for individuals and their environment. The aims of this research are:to find out the cultural values ​​of Siri' Na Pacce among the administrators of the Nuruddin Temappa Mosque and ethical accounting practices in financial management carried out by the financial administrators of the Nuruddin Temappa Mosque. This research includes descriptive qualitative research using a phonomenological approach in collecting data using observation, documentation and interviews. The interview method is used to strengthen and deepen the study of the object under study. The focus of this research is on the Siri' Na Pacce culture and financial reporting of the Nuruddin Temappa Mosque, Suppa District, based on sharia accounting principles. Research results show that (1) The Siri' Na Pacce culture of the Temappa people dominates under the name Siri Na Pacce, or what they often call Akkasirikennga, and the Siri' Na Pacce culture which is associated with three valuesculture, namely; first, Ethical Values ​​where a person is taught to maintain self-respect and dignity as a native Bugis. Secondly, Aesthetic Value, a person's feeling of love for himself and not making mistakes that could make him humiliated or lowering his self-esteem, and thirdly, this Moral Value, if someone lowers their self-esteem they will not remain silent because it is called Siri' Na Pacce that they must defend their honor and dignity. (2) Accounting Ethics Practices are divided into 3 things, namely; Transparency, Honesty and Justice where the Takmir of the Temappa Mosque, in reporting the mosque's finances, carries out transparency (openness) by announcing the amount of the mosque's balance every time there is income and expenditure to the public so that there is no dishonesty in recording financial reports. The Temappa people always prioritize justice because to the highest degree a person can be, if they have made a fatal mistake, they will receive the treatment they should receive.